The Effect of Land-Use on Herbaceous Production and Grazing Capacity in the Molopo District of the North West Province, South Africa - Jordaan, Franci; Rooyen, Jaco Van (International Journal of Sustainable Agricultural Research, 2020)
There are three main types of rangeland management systems in South Africa, namely commercial livestock farming, communal livestock farming and game farming. In commercial farming you normally find one manager/owner with a specific management plan, whilst communal farming is characterized by numerous land users with no specific management plan. The communal areas are also normally overstocked and this overstocking leads to rangeland degradation. In this study the effect of two land-uses (commercial and communal) on herbaceous production and grazing capacity were studied. It was clear from the results that the herbaceous production of the communal rangelands was lower than that of the commercial rangelands. The grazing capacity figures showed that sustainable farming practices were also not possible if the communal rangeland is in a poor condition – this was not even possible in good rainfall years.